2023
DOI: 10.1093/ibd/izad001
|View full text |Cite
|
Sign up to set email alerts
|

Gender Biases and Diagnostic Delay in Inflammatory Bowel Disease: Multicenter Observational Study

Abstract: Background Female gender could be a cause of diagnostic delay in inflammatory bowel disease (IBD). The aim of this study was to investigate the diagnostic delay in women vs men and potential causes. Methods This multicenter cohort study included 190 patients with recent diagnosis of IBD (disease duration <7 months). Reconstruction of the clinical presentation and diagnostic process was carried out in conjunction with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Based on our results, although psychological support should be offered to all individuals with a recent diagnosis of IBD, people with special susceptibility to emotional disorders should be intensively monitored for emotional impairment and prioritized for early psychological support. Gender differences in the course and presentation of IBD have already been reported (Greuter et al, 2020;Sempere et al, 2023). Women are more prone to develop anxiety and mood disorders than men (Asher et al, 2017) However, this specific frailty found in women with IBD regarding psychological impairment should be specifically addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our results, although psychological support should be offered to all individuals with a recent diagnosis of IBD, people with special susceptibility to emotional disorders should be intensively monitored for emotional impairment and prioritized for early psychological support. Gender differences in the course and presentation of IBD have already been reported (Greuter et al, 2020;Sempere et al, 2023). Women are more prone to develop anxiety and mood disorders than men (Asher et al, 2017) However, this specific frailty found in women with IBD regarding psychological impairment should be specifically addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Gender inequities leading to delayed diagnosis or misdiagnosis were found on all levels of the healthcare system. 29 Other studies did not find gender to be a risk factor for DD. 8,9,12,[22][23][24] LOCALIZATION OF DISEASE Ileal localization of the disease was found to be a significant risk factor for DD, largely attributable to the ileal CD presenting with mild and unspecific symptoms, including abdominal pain, less frequent diarrhea, and absence of rectal bleeding.…”
Section: Age At Diagnosismentioning
confidence: 95%